Health and Well-Being in Surviving Congenital Heart Disease Patients: An Umbrella Review With Synthesis of Best Evidence - Cocomello, Lucia; Taylor, Kurt; Caputo, Massimo; Cornish, Rosie P.; Lawlor, Deborah A. (Frontiers in Cardiovascular Medicine, 2022)
Background:Advances in the management of congenital heart disease (CHD) patients have enabled improvement in long-term survival even for those with serious defects. Research priorities (for patients, families and clinicians) have shifted from a focus on how to improve survival to exploring long-term outcomes in patients with CHD. A comprehensive appraisal of available evidence could inform best practice to maximize health and well-being, and identify research gaps to direct further research towards patient and clinical need. We aimed to critically appraise all available published systematic reviews of health and well-being outcomes in adult patients with CHD. Methods: We conducted an umbrella review, including any systematic reviews that assessed the association of having versus not having CHD with any long-term health (physical or mental), social (e.g., education, occupation) or well-being (e.g., quality of life (QoL)) outcome in adulthood (≥18-years). Results: Out of 1330 articles screened, we identified five systematic reviews of associations of CHD with adult outcomes. All but one (which studied QoL) explored health outcomes: one cardiovascular, two mental, and one mortality after transplant. CHD patients had a higher risk of stroke, coronary heart disease and heart failure, with the pooled relative risk (RR) for any outcome of 3.12 (95% CI: 3.01 to 3.24),with substantial heterogeneity (I2=99%) explained by the outcome being studied (stronger association for heart failure) and geography (stronger in Europe compared with other regions). CHD patients had a higher risk of anxiety (OR=2.58 (1.45 to 4.59)), and higher mean scores for depression/anxiety symptoms (difference in means= -0.11 SD (−0.28 to 0.06), I2=94%)). Compared with patients having a cardiac transplant for other (non-CHD) diseases, CHD patients had higher short-term mortality (RR at 30-days post-transplant = 2.18 (1.62 to 2.93)),with moderate heterogeneity (I2=41%) explained by previous surgery (higher mortality with prior Fontan/Glenn operation).All domains of QoL were lower in patients with Fontan’s circulation than non-CHD adults. Conclusions:CHD Adults have poorer cardiovascular, mental health and QoL outcomes, and higher short-term mortality after transplant. The paucity of systematic reviews,in particular for outcomes such as education, occupation and lifestyles,highlights the need for this to be made a priority by funders and researchers.